WHAT ACTUALLY DRIVE CONSTRUCTION PROJECT PERFORMANCE FROM OPERATIONS MANAGEMENT PERSPECTIVE - Rachmad Irwanto (International Journal of Civil Engineering and Infrastructure, 2022)
Construction industry is always an interesting discussion topic. Some have it approached from its planning and scheduling view accommodating risk analysis. Other interesting topics related to construction industry are its business model, organization and operations. The author argues that construction is a function of them all. An emphasized study on a specific topic above would be less relevant given the fact that construction industry is highly fragmented. From literature review, factors such project integration, communications, knowledge and understanding, human resources, safety, financial, and cost management drive more significant impact on project scheduling performance